Effect of Autoclave Sterilization on the Number of Uses and Resistance to Cyclic Fatigue of WaveOne Gold and Four Replica-Like Endodontic Instruments - Gustavo Ragozzini; Amjad Abu Hasna; Fernando Antonio Siano dos Reis; Felipe Bernardo de Moura; Tiago Moreira Bastos Campos; Carlos Eduardo Silveira Bueno; Cláudio Antonio Talge Carvalho; Alexandre Sigrist de Martin (International Journal of Dentistry)
This study aimed to evaluate the effect of autoclave sterilization on the integrity and instruments’ fracture number after multiple uses and cyclic fatigue of the original WaveOne Gold (Dentsply Sirona Endodontics) compared to four replica-like instruments (TF4-Gold, Roll-Wave-Gold, W-File, and Micro-Gold). The instruments were analyzed by scanning electron microscope (SEM) before being used in root canal instrumentation (baseline). One hundred and fifty human molars, freshly extracted for orthodontic reasons or periodontal disease and with severe curvature (between 30° and 60°), were used. Fifty teeth were instrumented with 10 instruments from each group and were evaluated for integrity. After sterilization in an autoclave, the instruments were analyzed by SEM. This procedure was repeated twice more, totaling three rounds of instrumentation, sterilization, and SEM analysis. Ten unused instruments from each group were evaluated for resistance to cyclic fatigue in a static test using a motor and a device simulating a canal with a 60° curvature angle. The instruments were driven by the motor until separation, visually verified, and the time measured in seconds. Data were analyzed by Chi-square, one-way ANOVA, and Tukey analysis, considering a significance level of 5%. It was found that there was no statistically significant difference between the groups tested in the effect of sterilization on the number of uses. The SEM analysis showed distortions in the instruments after the 3rd use. There was a statistically significant difference in the cyclic fatigue test between the results of WaveOne Gold, TF4 Gold, and Roll Wave Gold compared to W File and Micro Gold (P <0.0001) and a statistically significant difference between the W File and Micro Gold groups (P <0.0001). In conclusion, this study affirmed that WaveOne Gold, TF4-Gold, and Roll-Wave-Gold instruments exhibit comparable cyclic fatigue resistance. Besides, all examined instruments can be reliably employed for up to two cases.